Pumilio-dependent localization of mRNAs at the cell front coordinates multiple pathways required for chemotaxis. Issue 1 (December 2017) - Hotz, Manuel; Nelson, W.
Abstract Chemotaxis is a specialized form of directed cell migration important for normal development, wound healing, and cancer metastasis. In the social amoebaDictyostelium discoideum, four signaling pathways act synergistically to maintain directional cell migration. However, it is unknown how these pathways are coordinated in space and time to achieve persistent chemotaxis. Here, we show that the mRNAs and proteins of these four chemotaxis pathways and actin are preferentially enriched at the cell front during dynamic cell migration, which requires the Pumilio-related RNA-binding protein Puf118. Significantly, disruption of the Pumilio-binding sequence in chemotaxis pathway mRNAs, or mislocalization of Puf118 and its target mRNAs to the cell rear perturbs efficient chemotaxis in shallow cAMP gradients, without affecting the abundance of the mRNAs or encoded proteins. Thus, the polarized localization of Puf118-bound mRNAs coordinates the distribution of different chemotaxis pathway proteins in time and space, leading to cell polarization and persistent chemotaxis. Chemotaxis during differentiation ofDictyostelium discoideum requires four signalling pathways to maintain directional cell migration, but it is unclear how they are coordinated. Here the authors show that the RNA-binding protein Pumilio localizes mRNAs and proteins of these pathways and actin at the cell front during dynamic cell migration.